Aproximación difusa con filtros de orden bajo a filtros de orden alto aplicados a señales ECG - Villa A, Carlos; Reyna C., Marco Antonio; Villa A., Rafael (Revista Mexicana de Ingenieria Biomedica, 2004)
To process biological signals is necessary to discriminate between the true information and the noise induced by the environment and the acquisition instruments. Generally, an automatic acquisition system this task is achieved by implementing digital filters which transfer function is approximated as much as possible to the ideal transfer function. The requirements of the algorithms to implement the filters are imposed by the characteristics of the biological signals. These signals are low-frequency signals mixed with noise from different sources such as the 50/60 Hz. noise induced by the environment, noise generated by the acquisition instruments, wideband noise due to the quantization and analog-digital conversion of the signals, and noise generated from different biological sources not considered by our analysis. When the goal is to process a huge amount of information spending as minimum time as possible we can design low order filters sacrificing the frequency response of the filter. In this paper, we present the development of an algorithm to calculate the coefficients of a low-order low-pass filter. We present a fuzzy approximation of a high-order filter to a low-order filter. In this work, we present the results obtained playing the filter to ECG signals, especially in the detection of the QRS, P and T waves immersed in noisy signals